2023
DOI: 10.22541/essoar.167979224.40405342/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nyiragongo crater collapses measured by multi-sensor SAR amplitude time series

Abstract: Crater morphology at active volcanoes can change rapidly. Quantifying changes during the course of a volcanic unrest episode may help assess the level of volcanic activity. However, limitations such as crater accessibility, cloud cover or intra-crater eruptive activity may hamper regular optical or on-site crater monitoring. Here we use multi-sensor satellite Synthetic Aperture Radar (SAR) imagery to produce dense time series of quantitative indicators of crater morphological changes. High temporal resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Using colocated seismo-acoustic records at KBTI over ∼2 years (September 2015-November 2017), Barrière et al (2018) identified long-period (<2 Hz) repetitive seismic events and continuous tremor (i.e., 2023) for more details). PickCraterSAR data are smoothed with a ±1 day moving average window (Smittarello et al, 2023) or ±7 days for updated results based on COSMOSkyMed images only. (c) Space-based daily solutions for SO 2 emissions obtained from TROPOMI and thermal hotspots associated to Nyiragongo (S2 stands for Sentinel-2, L8/9 for Landsat-8/9).…”
Section: Characteristics Of Nyiragongo's Infrasound Signaturementioning
confidence: 99%
See 4 more Smart Citations
“…Using colocated seismo-acoustic records at KBTI over ∼2 years (September 2015-November 2017), Barrière et al (2018) identified long-period (<2 Hz) repetitive seismic events and continuous tremor (i.e., 2023) for more details). PickCraterSAR data are smoothed with a ±1 day moving average window (Smittarello et al, 2023) or ±7 days for updated results based on COSMOSkyMed images only. (c) Space-based daily solutions for SO 2 emissions obtained from TROPOMI and thermal hotspots associated to Nyiragongo (S2 stands for Sentinel-2, L8/9 for Landsat-8/9).…”
Section: Characteristics Of Nyiragongo's Infrasound Signaturementioning
confidence: 99%
“…The absence of observable lava-related thermal anomaly was noticed one day later on 1 June 2021 (Figure S7 in Supporting Information S1). This date corresponds to the deepest crater bottom after successive deepening and enlarging of the pit crater (∼580 m deeper than before the eruption), after which the crater refilled the crater bottom from collapsing walls (Smittarello et al, 2023). Both renewal of intra-crater activity on 28 September and 25 November 2021 are clearly identified in the infrasound records, further validated by thermal imagery on 29 September despite very cloudy conditions (Figure S8 in Supporting Information S1) or by visual inspection on 1 October (Figure 2a).…”
Section: Nyiragongo's Eruptive Activity In the Period 2018-2022mentioning
confidence: 99%
See 3 more Smart Citations